A Sociolinguistic Analysis of Code-Mixing in YouTube Podcast Discourse: The Case of Naura Ayu - Utari, Siti Amaliana; Zulferdi, Lazuar Azmi (International Journal of Research in Education, 2026)
Code-mixing has become a pervasive linguistic phenomenon in both spoken and digital communication, where speakers combine elements from different languages in a single discourse. In multilingual contexts such as Indonesia, code-mixing reflects speakers’ linguistic creativity and social identity. However, despite its increasing occurrence on social media, limited research has examined how code-mixing practices are shaped by situational factors and communicative intentions in online podcast interactions. This study aims to identify the types and factors of code-mixing based on Hoffman’s (1991) framework found in a YouTube video podcast on the Puella ID channel, focusing on the speaker Naura Ayu, an Indonesian actress. Employing a qualitative descriptive method following Sudaryanto’s (2015) analytical model, data were collected through systematic recording and transcription techniques from a single episode entitled Masa Lalu Naura yang Gak Kamu Tahu (aired on May 16, 2021). A total of 45 instances of code-mixing were identified and analyzed through categorization, verification, investigation, and conclusion stages. The findings indicate that intra-sentential code-mixing is the most dominant (31 instances), followed by intra-lexical mixing (4 instances) and pronunciation changes (3 instances), with six complex cases involving overlapping features. The analysis further reveals two main influencing factors: the discussion of particular topics and the speaker’s intention to emphasize ideas. These linguistic choices demonstrate how code-mixing functions not merely as a linguistic habit but as a deliberate communicative strategy to enhance rhetorical effect, express identity, and achieve discourse fluency.